Airbrush Spray Coating of Amorphous Titanium Dioxide for Inverted Polymer Solar Cells. (25th November 2012) - La Notte, Luca; Salamandra, Luigi; Zampetti, Andrea; Brunetti, Francesca; Brown, Thomas M.; Di Carlo, Aldo; Reale, Andrea
Abstract : One of the main topics of organic photovoltaics manufacturing is the need for simple, low cost, and large area compatible techniques. Solution-based processes are the best candidates to achieve this aim. Among these, airbrush spray coating has successfully applied to deposit both active and PEDOT layers of bulk-heterojunction solar cells. However, this technique is not yet sufficiently studied for interfacial layers (electron and hole transporting layers or optical spacers). In this paper, we show that amorphous titanium dioxide (TiO x ) films, obtained with an airbrush from a solution of titanium (IV) isopropoxide diluted in isopropanol, are successfully deposited on glass and PET substrates. Good surface covering results from the coalescence of droplets after optimizing the spray coating system. Simple inverted polymer solar cells are fabricated using TiO x as electron transporting layer obtaining encouraging electrical performances (η = 1.54 % on glass/FTO and 0.7% on PET/ITO substrates).